Konstruksi Epistemologi Fikih Pandemik: Analisis Fatwa-Fatwa MUI - Supena, Ilyas (Fakultas Syariah IAIN Purwokerto, 2021)
The Covid-19 pandemic has changed the behavior of people in the world, both in social, political, cultural and religious practices. The practice of strict health protocols has changed religious practices, both in Islam, Christianity, Hinduism, Buddhism and other faiths. In Islamic countries or countries where the population is predominantly Muslim, the ulama play an important role in legitimizing these changes in religious practice. In Indonesia, there is the Indonesian Ulema Council (MUI) which plays a role in providing fatwas related to changes in religious practices, such as prayer, zakat, Hajj and burying people who died due to being infected with Covid-19. These fatwas raise the issue of the epistemological construction that underlies the fatwas. Through a philosophical approach and content analysis of the MUI fatwas products, it was found that MUI fatwas were based more on empirical-scientific arguments (burhani) as well as ethical principles of Islamic teachings contained in the principles of maslahah (general good) and syadz al-zari'ah (avoiding danger). This article shows that the legal reasoning built by MUI shows the tendency of epistemology with a realism style based on scientific facts so that religion plays a role in providing legitimacy in the ethical and moral realm in the form of sharia objectives (maqÃ„Âshid al-syarÃ„Â«Ã¢â‚¬â„¢ah).